Triazole hybrids as new type of anti-fungal agents - Pankaj B. Miniyar; Anand A. Mahajan; Santosh N. Mokale; Mauli U. Shah; Ashish S. Kumar; Ganesh U. Chaturbhuj (Arabian Journal of Chemistry, 2017)
The present work involves synthesis of novel anti-fungal agents containing triazole scaffold. The newly designed compounds were synthesized on the trails of ketoconazole using the molecular hybridization approach. A series of 10 compounds having (2-((1H-1,2,4-triazol-1-yl)methyl)-2-(2,4-dichlorophenyl)-1,3-dioxolan-4-yl)methyl esters (4a–j) were prepared by conventional synthetic approach. The synthesized compounds were subjected for in vitro anti-fungal screening against Aspergillus niger, Aspergillus fumigatus, Candida albicans and Penicillium notatum. Out of 10 newly synthesized compounds, six compounds (4b–f and j) showed remarkable anti-fungal activity (MIC range 6.5–25 μg/ml), whereas compound 4d (MIC 6.5 μg/ml) was more potent than standard drug ketoconazole (MIC 12.5 μg/ml). These triazole hybrids can be considered as potential anti-fungal agents.